(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A simple, rapid, economical, precise and accurate RP-HPLC method for simultaneous estimation of Remogliflozin Etabonate and Metformin HCl in their tablet dosage form has been developed. The separation was achieved by C18 (4.6 mm X 10 cm) column containing packing L1 and HPLC Grade water: methanol (60:40) as mobile phase, at a flow rate of 0.7 ml/min. Detection was carried out at 230 nm. Retention time of Remogliflozin etabonate and Metformin HCl were found to be 4.351 min and 3.294 min respectively. The method has been validated as per ICH guidlines for linearity, accuracy, repeatability, precision, and robustness. Linearity observed for Remogliflozin etabonate 20-100 μg/ml and for Metformin HCl100-500 μg/ml with correlation coefficient greater than 0.999. Developed method was found to be accurate, precise and rapid for simultaneous estimation of Remogliflozin etabonate and Metformin HCl in their Synthetic Mixture.